Oral health condition and chewing pattern of adult patients treated at the bariatric service of the Clinical Hospital of the Federal University of Pernambuco - Duarte, Maria das Graças; Kreimer, Flávio; Santos, Leonardo Cavalcanti Bezerra dos; Correia, Maria da Conceição de Barros; Nascimento, Zilma Ribeiro do; Marques, Kátia Maria Gonçalves; Lima, Niedje Siqueira de; Fontes, Luciana de Barros Correia (Seven Editora, 2024)
Introduction: Obesity represents a serious public health problem worldwide, as it is associated with comorbidities and a reduction in the quality of life of individuals with this condition. The increase in the incidence of this multifactorial disease has led to a growing demand for services with surgical interventions, even minimally invasive, generally known as bariatric surgery or gastroplasty. These procedures are more directed to patients who have not achieved success in clinical treatment for a minimum period of two years, according to clinical protocols and with a Body Mass Index greater than 35 kg/m². Objective: To report the experiences of interdisciplinary evaluations and interventions, by Speech-Language Pathology and Audiology and Dentistry, regarding the chewing pattern of adult patients assisted at the Bariatric Service of the Hospital das Clínicas, in the city of Recife. Proposing Institution or Service: Federal University of Pernambuco. Target audience: 20 adult patients, in the preoperative period for Bariatric Surgery, of both sexes and aged between 18 and 59 years. Individual or collective actions: The activities directed to this group of patients are established by kits, which involve the various specialties involved in the care of this specific group and for which Speech Therapy was inserted, requesting the participation of Dentistry. There is a joint analysis, both for the preoperative opinion and for the search for strategies to solve the treatment needs or conditions with negative repercussions for the performance of the masticatory function. These experiences took place between March 2022 and April 2023. Results obtained: In addition to the technical opinions, there was dental treatment of needs related to minor oral surgery, periodontal disease and the need for restorative or endodontic treatment; The greatest challenge is the oral rehabilitation of these individuals, due to the absence of many dental elements or units. DOI:https://doi.org/10.56238/sevened2024.007-070